Effects of acceptance of enlightenment on COVID-19 transmission using homotopy perturbation method - Ayoola, Tawakalt Abosede; Kolawole, Mutairu Kayode; Popoola, Amos Oladele (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
The deadly Corona virus disease has had a significantly devastating impact on the general public, necessitating the study of transmission dynamics. A mathematical model of a non-linear differential equation for COVID-19 infection is investigated with the effects of some basic factors, such as the acceptance of enlightenment to avoid being exposed and the acceptance of enlightenment to go for vaccination. The basic reproduction number, which determines the disease's spread, is calculated. The local and global stability analyses of the model are carried out. The sensitivity analysis is also computed. Numerical simulation using the homotopy perturbation method demonstrates the effect of the acceptance of enlightenment on the population. Our results indicate that when the populace accepts vaccination, the rate at which COVID-19 spreads reduces.